Performance, Carcass Production, and Meat Quality of Sumba Ongole Bulls Fed Ration Supplemented Velvet Bean (Mucuna pruriens) - S. M. Yantika; . Alamsyari; D. Evvyernie; D. Diapari; K. Winaga (Faculty of Animal Science, Bogor Agricultural University, 2016)
This research aimed to study performance, carcass production, meat quality, and economic feasibility of male Sumba Ongole cattle fed ration supplemented with velvet bean (M. pruriens). The research was designed in a completely randomized block design using 16 cattle with average body weight of 488+37.08 kg. The treatments were: T0= 15% straw + 85% concentrate; T1= T0 + 12% of velvet bean flour supplement; T2= T0 + 16% of velvet bean tempeh supplement; and T3= T0 + 200 mg/head/d of ractopamine hydrocloride. Data were analyzed by using analysis of variance with orthogonal contrast. The observed variables included feed consumption, average daily body weight gain (ADG), feed efficiency (FE), income over feed cost (IOFC), hot carcass weight (HCW), carcass percentage, subcutaneous fat thickness, meat pH, tenderness, cooking loss, and water holding capacity (WHC). The result revealed that the addition of 12% velvet bean flour into the rations increased dry matter consumption (P<0.05), but did not affect ADG, FE, IOFC, carcass production, and meat quality. The addition of 12% velvet bean flour produced the lowest cooking loss (P<0.05). The addition of 16% velvet bean tempeh into the rations significantly increased (P<0.05) dry matter consumption, however reduced (P<0.05) ADG, FE, and IOFC compared to control treatment. It is concluded that velvet bean flour at the level of 12% can be used as an alternative feed supplement in the ration of Sumba Ongole cattle and can replace the use of synthetic ß-agonist.